2015
DOI: 10.1371/journal.pone.0124987
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Early Disease Status in Treatment-Naive Male Paediatric Patients with Fabry Disease Enrolled in a Randomized Clinical Trial

Abstract: Trial DesignThis analysis characterizes the degree of early organ involvement in a cohort of oligo-symptomatic untreated young patients with Fabry disease enrolled in an ongoing randomized, open-label, parallel-group, phase 3B clinical trial.MethodsMales aged 5–18 years with complete α-galactosidase A deficiency, without symptoms of major organ damage, were enrolled in a phase 3B trial evaluating two doses of agalsidase beta. Baseline disease characteristics of 31 eligible patients (median age 12 years) were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 59 publications
3
29
0
4
Order By: Relevance
“…The presence of early cerebrovascular disease in children with FD has been described in previous reports. 26,27 Other early findings may include subtle electrocardiography abnormalities, mild left ventricular hypertrophy, and mild albuminuria. [28][29][30] In conclusion, sex, phenotype, and plasma lysoGb3 concentrations are strongly associated with the rate of clinical events as well as cardiac, renal, and cerebral involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of early cerebrovascular disease in children with FD has been described in previous reports. 26,27 Other early findings may include subtle electrocardiography abnormalities, mild left ventricular hypertrophy, and mild albuminuria. [28][29][30] In conclusion, sex, phenotype, and plasma lysoGb3 concentrations are strongly associated with the rate of clinical events as well as cardiac, renal, and cerebral involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of kidney biopsies in the diagnosis, classification and assessment of therapeutic efficacy in Fabry disease has recently been highlighted in several studies and case series [3,7,12,16,20], as well as in a recent KDIGO conference report [4]. There is increasing evidence that accumulation of Gb3 in podocytes is an early marker of potential progressive Fabry nephropathy, and several studies have shown that prominent histological changes appear far earlier than clinical renal symptoms or albuminuria [21,22]. Secondary changes in the filtration barrier may be a plausible mechanism for progressive structural and functional damage.…”
Section: Discussionmentioning
confidence: 99%
“…One further long-term and one small short-term study assessed skin Gb3 under ERT and showed partial clearance [10,30]. In a recent study using electron microscopy, Gb3 deposits were described and semiquantitatively assessed in treatment-naïve male pediatric FD patients [8]. Interestingly, Gb3 was found in superficial skin capillary endothelial cells and deep vessel endothelial cells of the majority of these young male patients, which is quantitatively similar to our findings with 53% male patients showing Gb3 deposits of >0.05% ROI in distal skin, however, with less spatial resolution as a disadvantage of the method.…”
Section: Discussionmentioning
confidence: 99%
“…In skin, Gb3 may accumulate in vascular endothelium, smooth muscles, fibroblasts, and eccrine sweat glands [28] and it has been localized to lysosomes using electron microscopy [9]. In a phase 3 clinical trial on enzyme replacement therapy (ERT), clearance of Gb3 was shown from vascular endothelium and to a lesser degree from dermal smooth muscle cells and perineurium [10].…”
Section: Introductionmentioning
confidence: 99%